2021
DOI: 10.3390/su132111668
|View full text |Cite
|
Sign up to set email alerts
|

Natura 2000 Network vs. Tourism and Investment Potential of Communes—A Case Study of Czarnkowsko-Trzcianecki County

Abstract: The Natura 2000 is a network of protected areas established in the European Union on the basis of EU Directives. Simultaneously it is the youngest form of protected areas in Poland. Hence conflicts between conservation objectives and opportunities as well as needs of community economic development are quite common. The aim of the present study was to evaluate the tourism and investment potential of Czarnkowsko-Trzcianecki County and determine whether the Natura 2000 network is a factor in increasing the touris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 16 publications
(29 reference statements)
0
8
0
Order By: Relevance
“…Researchers have described the role of destination attributes [5]. The perceived attributes starting with tourist attractions [4] and end with the different levels of attraction for investment [6,7] or with quality indicators such as struc- Positive linear growth in the number of studies can be observed in the graph, with an appreciable jump between 2021 and 2023. In addition, a great deal of research has involved the development of different tools or of other complementary scientific branches.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Researchers have described the role of destination attributes [5]. The perceived attributes starting with tourist attractions [4] and end with the different levels of attraction for investment [6,7] or with quality indicators such as struc- Positive linear growth in the number of studies can be observed in the graph, with an appreciable jump between 2021 and 2023. In addition, a great deal of research has involved the development of different tools or of other complementary scientific branches.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have described the role of destination attributes [5]. The perceived attributes starting with tourist attractions [4] and end with the different levels of attraction for investment [6,7] or with quality indicators such as structural quality, ecological quality, and management quality [8]. Other quality variables include the quality of the country's promotion, information, accommodation, and restaurants [9].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations